Relational autonomy in pediatric healthcare: A scoping review - Matthiesen, Amarens (Nursing ethics, 2026)
Background The concept of relational autonomy has gained popularity for accentuating the social embeddedness of autonomy. In pediatrics, relational autonomy provides a framework for conceptualizing the complexities of healthcare processes, such as shared decision-making and children?s transitions to adult care systems. However, a lack of clarity exists regarding how to define and operationalize relational autonomy in pediatric healthcare. To our knowledge, no reviews of literature have been conducted to better understand this concept in pediatrics and guide further research.Research Aim The purpose of this scoping review was to describe literature focusing on relational approaches to autonomy in the context of pediatric healthcare.Research design A scoping review methodology proposed by Arksey and O?Malley and the Joanna Briggs Institute guided this review. Seven databases were searched for literature published between 2004 and 2024. Out of 2895 potentially relevant publications, a total of 28 articles were included for review.Ethical Considerations This study was conducted and reported in accordance with recognized scientific scoping review guidelines.Findings Various terms were used to describe relational approaches to autonomy in pediatrics. These terms shared a common goal of promoting a more holistic view of children and their decision-making processes in pediatric care. Most articles relied on adult perspectives (e.g., caregivers and healthcare providers) to shed light on shared decision-making processes. The perspectives of children and nurses were underrepresented in the literature, especially in the context of the Global South.Conclusion Additional research is needed to capture the lived experiences of a wider range of individuals with developing and exercising autonomy using diverse research methods. As the perspectives of nurses and children remain excluded from literature, new knowledge on their experiences with autonomy can inform the delivery of care that is ethically and morally sound.